Role of Women in Higher Education in the Digital Age: Analysis of Challenges and Gender Equality - Masir Ibrahim; Maramita Elfani (Journal Discrimination and Injustice, 2025)
This research is a literature study with a descriptive qualitative approach that aims to answer three main questions: What is the role of women in higher education in the digital era? What are the challenges faced by women in this context? And what strategies can be applied to realize gender equality in higher education environments? Data were obtained from various scientific publications, policy reports, and relevant journal articles. The findings show that women face challenges in the form of gender stereotypes, limited access to technology, and double domestic burdens. On the other hand, the digital era also opens up opportunities through online learning, digital literacy training, and strengthening  moreover  inclusive academic leadership. The conclusion emphasizes the importance of equality strategies based on values ​​of justice, as well as the application of the concept of Mubādalah as a relational approach that can form a fair and gender-responsive higher education system.